Amor, empatía y conductas prosociales: una reflexión interdisciplinaria - López Arboleda, Gloria María (Universidad Católica Luis Amigó, 2022)
This book presents, through reflection, the relevance, timeliness and necessity of love, empathy and prosocial behaviors within the framework of the professional and disciplinary work of the authors. The reader will be able to find here what these professionals, academics and intellectuals think and feel about it. Let the reader know that it was not a simple writing project, maybe because of the invitation to think about oneself, maybe because of the presence of the concept of "love" in the academy, or maybe, because we are not so accustomed to putting in the first person the reflection turned from what we relate to day by day. May this text be the excuse to continue to reflect on the role of love, empathy and prosocial behavior in a world that sometimes shows great desolation. May these unknotted reflections allow us to understand and resignify, learn and continue.